DEFB1 rs11362 Polymorphism and Risk of Chronic Periodontitis: A Meta-Analysis of Unadjusted and Adjusted Data - Shao, Jun; Zhang, Miao; Wu, Lan; Jia, Xiao-Wei; Jin, Ying-Hui; Zeng, Xian-Tao (Frontiers in Genetics, 2019)
Objective: Chronic periodontitis (CP) is a growing problem that affects the worldwide population, having significant impacts on people’s daily lives and economic development. Genetics is an important component in the determination of individual susceptibility to periodontal diseases. Numerous studies have been performed to investigate the association between beta defensin 1 (DEFB1) rs11362 polymorphism and risk of CP, but the results are still inconclusive. Therefore, we conducted this meta-analysis to ascertain whether this variation in DEFB1 is associated with CP susceptibility. Methods: The relevant studies were searched in PubMed and Chinese National Knowledge Infrastructure (CNKI)databases up to January 9, 2018. Two independent authors selected citations and extracted the data from eligible studies. Odds ratios (ORs) with their 95% confidence intervals (95% CIs) were used to assess the strength of the association. Results: Seven case-control studies were included in this meta-analysis. Based on unadjusted data, there was no obvious association between DEFB1 rs11362 polymorphism and CP risk in all genetic models(A vs. G: OR=0.86, 95%CI=0.61-1.20; AA vs. GG: OR=0.83, 95%CI=0.50-1.39; AG vs. GG: OR=1.01, 95%CI=0.73-1.39; AG+AA vs. GG: OR=0.91, 95%CI=0.74-1.11; and AA vs. AG+GG: OR=0.83, 95%CI=0.57-1.21); the results of adjusted data also showed no significant relationship. Subgroup analyses based on ethnicity, participants’ smoking status, HWE in controls and severity of CP all revealed similar results to that of the overall analysis. Sensitivity analysis indicated the results were robust and no evidence of publication bias was found. Conclusions: Our meta-analysis suggests that DEFB1 rs11362 polymorphism may not have an important effect on the risk of CP. Further large-scale and well-designed studies are necessary to validate our conclusion in the future.